A comparative study of bone remodeling around hydroxyapatite-coated and novel radial functionally graded dental implants using finite element simulation. (April 2022) - Jafari, Bahram; Katoozian, Hamid Reza; Tahani, Masoud; Ashjaee, Nima
Abstract: This comparative study simulates bone remodeling outcome around titanium dental implants and compares the final bone configuration with the one around novel implants composed of radial functionally graded materials (FGMs) and the titanium implants with hydroxyapatite (HA) coating. A dental implant system embedded in 3D mandibular bone with masticatory loading was simulated by the finite element method. A bone remodeling algorithm was applied to cancellous and cortical bones. Young's modulus and von Mises stress were obtained to ensure bone homeostasis and evaluate the final bone configuration. Local stress distribution in the bone-implant interface was analyzed before and after bone remodeling. The average final Young's modulus of cancellous bone reached 2.68, 2.49, and 2.32 GPa for the FGM, HA-coated, and the titanium models, respectively. These values for cortical bone were 17.75, 16.86, and 17.20 GPa in the same order. Radial FGM implants generated the highest remodeling stimulus and bone density. Their superiority over the HA-coated models was confirmed by four implant surface stiffness values (10, 20, 30, and 40 GPa). Remodeling increased bone density around the implant, consistent with clinical data and reduced stress concentration in the cortical neck. The stress values were in the safe zone regarding overload-induced bone resorption. The findings of this study were substantiated by clinical images and bone density values from previous literature.